PENGARUH STORYTELLING TERHADAP IDENTITAS MEREK DAN KETERLIBATAN KONSUMEN DI PLATFORM DIGITAL - Nathaneil, Kimberly (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN (COMMUNITY OF RESEARCH LABORATORY), 2025)
In an increasingly saturated digital environment, storytelling has been identified as a fundamental strategic approach for resonating with audiences. This research empirically investigates the influence of storytelling on the perception of digital marketing performance, positing brand identity and consumer engagement as key mediating mechanisms. Employing a quantitative methodology, survey data were collected from 100 digital platform users in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that storytelling lacks a direct statistical influence on perceived performance; this relationship is, instead, fully mediated through brand identity and consumer engagement. Both mediation pathways were found to be significant, with consumer engagement emerging as the more dominant mechanism. The study concludes that the efficacy of digital storytelling is contingent upon its capacity to first cultivate a strong brand identity and foster deep audience engagement, thereby translating narrative efforts into positive marketing outcomes.